A ANALISIS LAYANAN DIGITAL PLN MOBILE TERHADAP KEPUASAN PELANGGAN PADA PT PLN (PERSERO) ULP KOTA METRO: ANALISIS LAYANAN DIGITAL PLN MOBILE TERHADAP KEPUASAN PELANGGAN PADA PT PLN (PERSERO) ULP KOTA METRO - A'an Suhandi (Universitas Muhammadiyah Metro, 2026)
The large number of customers in Metro City and the number of technical service officers and vendors causes the ratio of service from officers to customers to be less than optimal, so that in improving the quality of service provided by PLN is by using an online system, namely by using an application. The purpose of this study is to determine the level of service quality performance, to determine the attributes of service quality that are considered important in determining customer satisfaction and to determine the factors that can influence the formation of customer satisfaction at PT PLN (Persero) ULP Metro City. This study uses a quantitative descriptive research approach to describe the performance of service quality and the importance of service quality in determining customer satisfaction. The data analyzed were generated from data collection through a service quality questionnaire with five indicators, namely physical evidence, reliability, responsiveness, assurance, and empathy. Data were collected by scoring answers with a score of 1-5. The data that had been obtained was then analyzed using the IPA (Importance Performance Analysis) method.